Death : only for those who shall die--a yogi's guide to living, dying, and beyond - Vasudev, Jaggi, Sadhguru (Harmony, 2025)
This insightful exploration of death challenges conventional views, offering a spiritual perspective that encourages living fully by embracing death as an essential part of life while providing practical guidance on dying with purpose and supporting others through their journey.